The Influence of Creative Problem-Solving Learning Models on Students' Creative Thinking Skills related Temperature and Heat - Baharuddin, Fitriani; Nurazmi; Fiskawarni, Tri Hastiti (Program Studi Tadris IPA, Fakultas Tarbiyah (IAIN) Kediri, Indonesia, 2024)
One of the skills needed to face the 21st century is creative thinking. The aim of this research is to find out whether there is a significant difference between the creative thinking skills of students who are taught using the creative problem-solving learning model and those taught using the conventional model. This type of research is quasi-experimental, with the research design used being a nonequivalent control group. The subjects in this research are all students in class XI MIA SMAN 14 Maros, with the sample being class XI MIA 2 as the experimental class and class controls, each numbering 34 people. The research instrument used was a creative thinking skills test instrument on temperature and heat materials. The results of this research show a difference in the average score of students' creative thinking abilities between the experimental class and the control class, namely 33.49 in the experimental class and 28.29 in the control class. From the results of the hypothesis test, it can be seen that there are differences in the creative thinking skills of experimental class and control class students using a significance level of α = 0.05. Based on the results of this research, it can be concluded that the physics creative thinking ability of students taught using the creative problem solving learning model is higher than the physics creative thinking ability of students taught using the conventional learning model.